Microbial strategies for lead remediation in agricultural soils and wastewater: mechanisms, applications, and future directions - Gul, Isma; Adil, Muhammad; Lv, Fenglin; Li, Tingting; Chen, Yi; Lu, Heli; Ahamad, Muhammad Irfan; Lu, Siqi; Feng, Wanfu (Frontiers in Microbiology, 2024)
High lead (Pb) levels in agricultural soil and wastewater threaten ecosystems and organism health. Microbial remediation emerges asis a cost-effective, efficient, and eco-friendly alternative to traditional physical or chemical methods for eliminating Pb remediation. Previous research indicates that micro-organisms employ various strategies to combat Pb pollution, including biosorption, bioprecipitation, biomineralization, and bioaccumulation. This study delves into recent advancements in Pb-remediation techniques utilizing bacteria, fungi, and microalgae, elucidating their detoxification pathways. This review presents a comprehensive overview of microbiological mechanisms employed in Pb remediation and investigates the factors influencing that influence Pb removal through specific case studies. It delvesinvestigates into how bacteria immobilize Pb by generating nanoparticles that convert dissolved lead (Pb-II) into less harmful forms to mitigate its adverse impacts. Furthermore, the current review explores the molecular-levelmolecular-level mechanisms and genetic engineering techniques through which bacteria microbes develop resistance to Pb. We outline the challenges and potential avenues for research in microbial remediation of Pb-polluted habitats, exploring the interplay between lead Pb and micro-organisms and their potential in Pb removal.